MSME Internationalization Strategy Towards Global Business Competition Case Study on CV. Dua Putri Sholehah “HUNAY” Probolinggo - Joni Hendra; Sudarmiatin Sudarmiatin; Rosmiza Bidin (International Journal of Economics and Management Research, 2024)
In the Indonesian economy, Micro, Small and Medium Enterprises are the business group that has the largest number and has proven to be resistant to various shocks from the economic crisis. MSMEs are encouraged to be able to expand to the global market, not just on a national scale. Strategy is very important to determine the company's success in achieving its long-term goals. By choosing the right strategy for a particular company position, a company will have a competitive advantage. The aim of this research is to find out what is the most appropriate strategy for CV. Dua Putri Sholehah "Hunay" Probolinggo as MSMEs in facing global business competition. This research method uses SWOT analysis and IFAS, EFAS, by previously collecting data through interviews, questionnaires, observations and also literature studies. The results of this research indicate that the strategy that must be carried out by CV. Dua Ptri Sholehah "Hunay" is in quadrant I, namely the quadrant that supports an aggressive growth strategy which shows that this company has the strength to take advantage of existing opportunities, especially in export development. Currently the organization is in a strong condition so it is possible to continue to expand by opening branches to the countries it will target, increasing growth and achieving maximum progress.